Pendampingan Pelaku UMKM Wanita untuk Memaksimalkan Marketing melalui Aplikasi SiBakulJogja - Sri Wijayanti, Palupi; Wibawa; Mulat Widyastuti, Titik (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2021)
During this pandemic, several creations and innovations are needed to disseminate the productsand services provided by MSME (UMKM) actors. This aims to increase their turnover so that theycan survive and rise even during a pandemic and slump. This situation encourages the PGRIYogyakarta University service team to do community service in increasing their knowledgeregarding the SiBakul Jogja application. This knowledge is in line with the advantages of thisapplication which can also be used as a choice to promote products and services that have beenprovided and produced on a wide scale throughout the people of Jogjakarta. In addition, thisapplication also received great support from the Jogjakarta provincial government so that userswill get free shipping that makes it easier for consumers. The stages of service are licensing,material preparation, material delivery, and mentoring. The four stages are carried outprocedurally so that everything goes according to plan. The results of the service implementationshow the enthusiasm of the service participants and have the impact that business owners who havesuccessfully registered their companies in the application can guide other participants.